Emperor Penguin's New Clothes (The) - Perlman, Janet (New York : Scholatic Inc, 1994)
What's black and white and proud as a peacock? The Emperor Penguin, the best dressed bird in the land! But pride won't save the Emperor from a pair of clever scoundrels, as they reveal the naked truth about the foolis ruler.
Keywords: Pride--Fiction; Foolishness--Fiction